Peran Forum Pustakawan dalam Pengembangan Profesionalisme Pustakawan di Lingkungan Universitas Gadjah Mada - Desy Natalia Anggorowati (Berkala Ilmu Perpustakaan dan Informasi, 2017)
This research discusses the role of Librarian Forum at UGM. The purpose of this paper is to examine  the role of Librarian Forum to develop professionalism and competence for librarians and to understand the inhibiting factors from librarians to actively involve themselves in the Forum. Using a descriptive qualitative approach, the data collection method was literature study and interviews. The result indicated that the role of Librarian Forum in the last 3 period: 2011-2013, 2013-2015 and 2015-2018 has been indicated important to support 4 competencies in SKKNI (Standar Kompetensi Kerja Nasional Indonesia). But of the 60 activities, the core competence of “conducting information literacy activities” showed  the highest. Challenges faced by the members to utilise the Librarian Forum as a professional development arena and competence was the schedule. Another challenges were that, the content of activities didnot match with what the members needed.